Performance Evaluation of Automated Urine Analyzers: Laura XL - Ratnakar, Parag J.; Shrirao, Tejaswini; Buch, Archana C; Gore, Charusheela R.; Shetty, Abhinav; Chandanwale, Shirish; Lalla, Poonam (South Eastern European Journal of Public Health, 2025)
Urinalysis is the third most used diagnostic screening test in clinical practice. Manual urine analysis is labor-intensive and requires experienced staff for accurate results and interpretation. New-generation automated urianalysers have been introduced with microscopic analysis. The aim of this study was to evaluate the results of LauraXL, automated Urine Analyzer and validate it with UF 4000 Sysmex and manual method. Method: A cross-sectional study was conducted on 107 urine samples. Laura XL works on image-based microscopy, whereas UF 4000 works on the principle of flow cytometry. Epithelial cells (EC), red blood cells (RBC), white blood cells (WBC), crystals, cast, and yeast from both machines were compared with manual microscopy. Results: The degree of concordance was analyzed. UF4000 showed greater agreement than Laura for WBC, EC, and Crystals, kappa as 0.420, 0.238, and 0.437 respectively (p <0.0001.) Yeast showed substantial agreement with kappa 0.650(UF 4000) and 0.643 (LauraXL). The agreement of Laura with Manual was greater than UF4000 for RBC (kappa 0.360 and p<0.0001). UF4000 revealed a sensitivity of >95% for WBC, EC, CAST, Crystal, and Yeast. Similar results were observed for Laura except for Crystal (sensitivity: 81%). Conclusion: Both automatic urine analyzers exhibited comparable performances and strongly correlated with manual microscopy. While manual urinalysis remains critical for diagnosis, automated systems offer enhanced efficiency, accuracy, and reliability, making them indispensable in modern clinical laboratories.